Evaluating the impact of concurrent sucrose availability on operant ethanol self-administration in male and female Long Evans rats - Olivia A. Ortelli; Jeffrey L. Weiner (Addiction Neuroscience)
Investigating how environmental factors, such as the availability of non-ethanol alternative reinforcers, influences ethanol self-administration is critical for understanding the pathology of alcohol use disorder (AUD). Here we established the first operant choice paradigm that leverages the strengths of the sipper tube self-administration model to investigate how concurrent access to sucrose altered ethanol self-administration in male and female Long Evans rats. Choice behavior was examined using two distinct paradigms, including a novel adaptation of the response requirement paradigm. Under both a fixed-ratio or response requirement paradigm, we observed that concurrent availability of an alternative reinforcer significantly reduced appetitive and consummatory ethanol drinking-related behaviors. Furthermore, we assessed the sensitivity of the response requirement choice paradigm by administering the pharmacological stressor yohimbine and by altering the taste of the ethanol solution. Yohimbine administration non-selectively increased ethanol and sucrose intake, but not seeking, while taste adulteration decreased ethanol seeking and intake. These experiments demonstrate the utility of two concurrent choice paradigms that can more accurately capture AUD-like phenotypes, such as ethanol-directed choice in the face of alternative reinforcers. Future studies should investigate how models of vulnerability and dependence alter ethanol choice behavior under these paradigms.